Tephrochronology of Bed II, Olduvai Gorge, Tanzania, and placement of the Oldowan–Acheulean transition. Issue 120 (July 2018) - McHenry, Lindsay J.; Stanistreet, Ian G.
Abstract: Tuffaceous marker beds, derived from volcanic products from the Ngorongoro Volcanic Highlands, help define a stratigraphic framework for the world-renowned fossil and stone tool record exposed at Olduvai Gorge, Tanzania. However, previous efforts to constrain this tuff record, especially for Olduvai Bed II, have been limited because of erosion, contamination, reworking, and the alteration of volcanic glass under saline-alkaline conditions. This paper applies previously defined geochemical and mineralogical "fingerprints" for several major Bed II marker tuffs, based on glass (where available) and phenocrysts more resistant to alteration (feldspar, hornblende, augite, and titanomagnetite), to tuffs from stratigraphic sections in the Olduvai Junction Area, including previously and recently excavated Acheulean and Oldowan sites (HWK EE (Locality (Loc) 42), EF-HR (Loc 12a), FLK (Loc 45), and MNK (Loc 88)). The Middle Bed II Bird Print Tuff (BPT) is found to be more compositionally variable than previously reported but is still valuable as a stratigraphic marker over short distances. The confirmation of blocks of Tuff IID in conglomerate helps constrain Upper Bed II stratigraphy at sites where in-situ tuffs are absent. This paper also compiles the results of published geochronological research, providing stratigraphic context and updating previously reported dates using a consistent 40 Ar/ 39 Ar reference standard age. The results of this work support the following paleoanthropologically relevant conclusions: 1) the early Acheulean site EF-HR (Loc 12a) is situated above the level of Hay's Tuff IIC, and thus sits in Upper rather than Middle Bed II, (2) the HWK EE (Loc 42) Oldowan site is constrained between Tuff IIA and Tuff IIB, just above the boundary between Lower and Middle Bed II, and 3) the Acheulean site at FLK W most likely lies within the Middle Augitic Sandstone, above Tuff IIB, similar to the placements by Leakey and Hay for the earliest Acheulean at Olduvai.